2023
DOI: 10.1126/scitranslmed.ade6023
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent impairment in antibody responses elicited by a homologous CoronaVac booster dose

Abstract: The emergence of the SARS-CoV-2 Omicron sublineages resulted in increased transmission rates and reduced protection from vaccines. To counteract these effects, multiple booster strategies were used in different countries, although data comparing their efficiency in improving protective immunity remain sparse, especially among vulnerable populations, including older adults. The inactivated CoronaVac vaccine was among the most widely distributed vaccine worldwide and was essential in the early control of SARS-Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…To capture the stratified effect of disease burdens in detail, the model divided the initial total cases averted into five stratified health metrics including symptomatic, asymptomatic, hospitalized, ICU, and death cases averted, and the statistics of these measures were calculated respectively based on the statistics data in (7) and (8). Additionally, the model assumed: (a) the population was homogenous and identical population size of each age group; (b) individuals with at least one dose vaccinated were infected with no symptoms (i.e., asymptomatic) due to partial immunity protection of vaccines; (c) the relative infectiousness of other types of infections was identical to the primary infections; (d) the primary vaccination was initiated at week 44, nearly eleven months after the establishment of the transmission; (e) to reflect seasonal variation in transmission, the model based seasonal reproduction numbers in this work on those used in (5), which calibrated values to yield the basic reproduction number of 2.3;…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To capture the stratified effect of disease burdens in detail, the model divided the initial total cases averted into five stratified health metrics including symptomatic, asymptomatic, hospitalized, ICU, and death cases averted, and the statistics of these measures were calculated respectively based on the statistics data in (7) and (8). Additionally, the model assumed: (a) the population was homogenous and identical population size of each age group; (b) individuals with at least one dose vaccinated were infected with no symptoms (i.e., asymptomatic) due to partial immunity protection of vaccines; (c) the relative infectiousness of other types of infections was identical to the primary infections; (d) the primary vaccination was initiated at week 44, nearly eleven months after the establishment of the transmission; (e) to reflect seasonal variation in transmission, the model based seasonal reproduction numbers in this work on those used in (5), which calibrated values to yield the basic reproduction number of 2.3;…”
Section: Methodsmentioning
confidence: 99%
“…Different countries enacted varied campaigns of vaccination in compliance with the objectives of health policies to balance the trade-offs between the health output of the populations and economic activities (2,3). Retrospectively, vaccines, transmission traits of the pathogen, and vaccination strategies had a combined impact on the risks of infections and subsequent health outcomes (5)(6)(7)(8)(9)(10). The data by WHO indicated that there were more than 100 vaccine candidates in clinical usage worldwide by 2023 (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational cohort studies of healthy adults ( 6 , 7 ) demonstrate that aging leads to baseline increases in plasma concentrations of pro-inflammatory cytokines ( 6 , 8 ), several of which, such as interleukin-6 (IL-6), are well-known biomarkers of COVID-19 severity, suggesting potential connections between the pathophysiology of human aging and COVID-19 ( 8 ). Juxtaposed against this state of aging-associated inflammation are functional impairments in innate and adaptive immune signaling observed during the vaccination of aged individuals ( 9 12 ). Furthermore, recent human in vitro data indicate that aging results in impaired production of type I interferons (IFNs) in monocytes and dendritic cells after Toll-like receptor (TLR) ligation, suggesting disrupted innate immunity ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observational cohort studies of healthy adults 5,6 demonstrate that aging leads to baseline increases in plasma concentrations of proinflammatory cytokines 5,7 , several of which (e.g., IL6) are well-known biomarkers of COVID-19 severity, suggesting potential connections between the pathophysiology of human aging and COVID-19 7 . Juxtaposed against this state of agingassociated inflammation are functional impairments in innate and adaptive immune signaling, observed during vaccination of aged individuals [8][9][10][11] . Furthermore, recent human in vitro data indicates that aging results in impaired production of type I interferons in monocytes and dendritic cells following Toll-like receptor (TLR) ligation, suggesting disrupted innate immunity [12][13][14][15][16] .…”
Section: Main Text: Introductionmentioning
confidence: 99%